A Monomeric GTPase-Negative MxA Mutant with Antiviral Activity - Janzen, Christian (American Society for Microbiology, 2000)
MxA is a large, interferon-induced GTPase with antiviral activity against RNA viruses. It forms large oligomers, but whether oligomerization and GTPase activity are important for antiviral function is not known. The mutant protein MxA(L612K) carries a lysine-for-leucine substitution at position 612 and fails to form oligomers. Here we show that monomeric MxA(L612K) lacks detectable GTPase activity but is capable of inhibiting Thogoto virus in transiently transfected Vero cells or in a Thogoto virus minireplicon system. Likewise, MxA(L612K) inhibited vesicular stomatitis virus multiplication. These findings indicate that MxA monomers are antivirally active and suggest that GTP hydrolysis may not be required for antiviral activity. MxA(L612K) is rapidly degraded in cells, whereas wild-type MxA is stable. We propose that high-molecular-weight MxA oligomers represent a stable intracellular pool from which active MxA monomers are recruited.